2019
DOI: 10.1186/s12978-019-0841-3
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for cluster randomized evaluation of reaching married adolescents - a gender-synchronized intervention to increase modern contraceptive use among married adolescent girls and young women and their husbands in Niger

Abstract: BackgroundEarly marriage and early childbearing are highly prevalent in Niger with 75% of girls married before age 18 years and 42% of girls giving birth between ages 15 and 18 years. In 2012, only 7% of all 15–19-year-old married adolescents (male and female) reported use of a modern contraceptive method with barriers including misinformation, and social norms unsupportive of contraception. To meet the needs of married adolescents and their husbands in Niger, the Reaching Married Adolescents (RMA) program was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Girls were considered eligible if they were: 1) aged 13–19 years old, 2) married, 3) fluent in Hausa or Zarma, 4) residing in the village where recruitment was taking place with no plans to move away in next 18 months or plans to travel for more than 6 months during that period, and 5) not currently sterilized. More information about study design and data collection can be found in the protocol paper for this study [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Girls were considered eligible if they were: 1) aged 13–19 years old, 2) married, 3) fluent in Hausa or Zarma, 4) residing in the village where recruitment was taking place with no plans to move away in next 18 months or plans to travel for more than 6 months during that period, and 5) not currently sterilized. More information about study design and data collection can be found in the protocol paper for this study [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional data used for this analysis were collected from April-June 2016 as part of the baseline survey for the Reaching Married Adolescents (RMA) Study [51]. This ongoing study employs a fourarm cluster randomised control design to evaluate the effects of multiple community-based approaches to expand access to modern FP methods among married adolescents in the Dosso region of Niger.…”
Section: Data Sourcementioning
confidence: 99%
“…We followed World Health Organization Guidelines related to minimizing risk of IPV when both a wife and husband were interviewed. This information is discussed further, elsewhere [35].…”
Section: Ethicsmentioning
confidence: 88%
“…Details of the sampling design and intervention can be found elsewhere. [35] Adolescent girls and young women and their husbands were eligible to participate in the study if an AGYW was a married 13-19 year old fluent in Zarma or Hausa. She could not be sterilized and could not have plans to move over the subsequent 18 months or travel more than 6 months across the study period.…”
Section: Study Data and Analytic Sample Formationmentioning
confidence: 99%